STUDY OF THE COVID-19 PANDEMIC ON RETURNS AND TRADING VOLUME ACTIVITIES OF STOCKS IN INDEX LQ45 INDONESIA STOCK EXCHANGE - Mustaruddin Saleh (JURNAL DIMENSI, 2022)
The purpose of the study is  to identify and analyze abnormal returns and trading volume activity at the announcement of the Covid-19 pandemic by President Joko Widodo on March 13, 2020. In this study, the authors try to exposed  the impact of the Covid-19 pandemic on the return and volume of trading activities which listed on the LQ45 index of the Indonesia Stock Exchange. The test results reveal that the announcement of the Covid-19 pandemic has a significant impact on abnormal returns and trading volume activity throughout the window period. These findings are in line with research conducted by He et al (2020), Xiong et al (2020) and Ashraf (2020) which revealed that the Covid-19 pandemic largely had a negative impact on stock prices listed on the stock exchange in their each  studies. respectively. Thus, this event study of the Covid-19 pandemic confirms research in various capital markets that the information content has a major impact on decreasing returns and volume of trading activity in various capital markets in the world.